PERCEPTION OF PORT SERVICE USERS ON QUALITY OF PORT OFFICE SERVICE (UPP) GARONGKONG KABUPATEN BARRU - Safaruddin; Muhammad Anwar (Meraja journal, 2022)
[Full Paper] to pdf Copyright (c) 2022 Meraja journal